2015
DOI: 10.1016/j.math.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diastasis recti abdominis from late pregnancy to 6 months postpartum, and relationship with lumbo-pelvic pain

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Mota, P., Pascoal, A. G., Carita, A., Bø, K. (2014). Prevalence and risk factors of diastasis recti abdominis from late pregnancy to 6 months postpartum, and relationship with lumbo-pelvic pain. Manual Therapy. doi:10.1016/j.math.2014.09.002Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.sciencedirect.com: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
92
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 29 publications
6
92
0
7
Order By: Relevance
“…Some studies, however, deny these statements. Sperstad et al [14] reported no difference between women with and without DRA in prevalence of low back pain, similarly as Mota et al [13] and Parker et al [21]. In Norwegian study, women with DRA did not have a weaker pelvic floor muscle or more pelvic floor dysfunctions than women without diastasis [22].…”
Section: Diastasis Recti Abdominismentioning
confidence: 80%
See 4 more Smart Citations
“…Some studies, however, deny these statements. Sperstad et al [14] reported no difference between women with and without DRA in prevalence of low back pain, similarly as Mota et al [13] and Parker et al [21]. In Norwegian study, women with DRA did not have a weaker pelvic floor muscle or more pelvic floor dysfunctions than women without diastasis [22].…”
Section: Diastasis Recti Abdominismentioning
confidence: 80%
“…Mota et al [13] and Sperstad et al [14] reported no association between DRA and the pre-pregnancy body mass index, weight gain, a baby's birth weight or abdominal circumference, heavy lifting, lifting and carrying children, and regular exercise.…”
Section: Diastasis Recti Abdominismentioning
confidence: 97%
See 3 more Smart Citations